1999
DOI: 10.1097/00001756-199904260-00035
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes induce several blood–brain barrier properties in non-neural endothelial cells

Abstract: The passage of immunocompetent cells across the blood-brain barrier (BBB) is regulated at the level of the cerebral capillaries which have specific morphological and biochemical properties. We have developed and characterized an in vitro model of the BBB using immortalized human endothelial cells (ECV 304) induced by rat astrocytes. In this model, endothelial cells are attached together by continuous intercellular junctions with numerous tight junctions, develop a permeability barrier having a significant tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 11 publications
2
49
1
Order By: Relevance
“…ZO and occludin molecules are shown to be primary regulatory proteins of tight junction that modulate BBB permeability [4]. Increased numbers of tight junctions in the presence of astrocytes or astrocyte CM have been demonstrated by the presence of inward ZO-1 expression [29,44,62]. We found that ZO-1 expression of HBMEC was increased in the presence of ACM (Fig.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…ZO and occludin molecules are shown to be primary regulatory proteins of tight junction that modulate BBB permeability [4]. Increased numbers of tight junctions in the presence of astrocytes or astrocyte CM have been demonstrated by the presence of inward ZO-1 expression [29,44,62]. We found that ZO-1 expression of HBMEC was increased in the presence of ACM (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…[1,35,39,44,61,62]. Astrocytes do not make direct contact with endothelial cells in vivo, but rather, are separated from endothelial cells by an extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…RAGE has been implicated in the pathogenesis of AD and diabetes-associated complications (37). Our results using ECV-304 cells, an in vitro model for the blood-brain barrier (BBB) (38,39), suggest a negative role of RAGE in the endothelial cell membrane resealing. Because RAGE is up-regulated under pathological conditions (e.g.…”
Section: Discussionmentioning
confidence: 74%
“…The TEER values for the "CO" samples were testified to be statistically significant higher than those of the other samples by one-way ANOVA analysis (α = 0.05). The TEER values were lower than the primary BBEC culture by Garberg et al which were 500-800 Ω cm 2 (7), but significantly higher than the ECV304 cell line (100 Ω cm 2 ), which has been used for feasible immortalized BBB models by several groups, and found to have relative high correlation between in vivo and in vitro permeability studies (44,87,88). As in vitro models, the TEER values were not expected to be as high as those found in in vivo environment, or even as high as the aforementioned primary cell cultures.…”
Section: Resultsmentioning
confidence: 83%
“…Previous research reported ECV304s were used for feasible immortalized bloodbrain barrier models (44,87,88). In this study, scientists used immortalized ECV304 and rat glioma (C6) both purchased from European Collection of Animal Cell Cultures (ECACC).…”
Section: Ecv304 Cell Linementioning
confidence: 99%